THE POLITICS OF LOCAL GOVERNMENT AUTONOMY IN NIGERIA RELOADED - Akpan, Felix; Ekanem, Okonette (European Scientific Journal, ESJ, 2013)
The politics of local government in Nigeria reloaded has been inspired by the 2013 Constitution amendment process initiated by the National Assembly. The main objective of the study is to intellectualize local government autonomy from a new perspective from the ones in extant literature. Using desk research and interview methods, the findings show that in both old and new federations the nature and character of the political system largely determine the kind of autonomy the central or regional or state government devolves to the local unit or local government. The study further shows that in Nigeria, the kind of autonomy the federal and state governments transfer to the local government is largely shaped by ethnicity and prebenal considerations. Also, that the suffocation and subversion of local government autonomy is more pronounced at the financial and leadership recruitment levels than in any other areas of intergovernmental relations. This explains why members of the political elite engage each other in a-tug-of-war over whose apron-string the local government should be tied to, rather than allow local governments operate autonomously. The study concludes that local government is a unique political structure and the degree of autonomy it enjoys from federal or regional or state government is congruent with the politics of the state. Consequently, there is no grand theory of local government autonomy that states can adopt and make amenable to their politics. Rather, the nature and character of state politics and the historical circumstances of its evolution throw up its own unique kind of local government autonomy.